Oral Melatonin Versus Placebo In Preoperative Anxiety Relief (Journal of Pharmaceutical Negative Results, 2023)
Before surgery and administration of anaesthesia, the patient goes through an unpleasant state which is called ‘preoperative anxiety.’ If left untreated, this is not only uncomfortable for the patient but is also associated with circulatory disturbances, psychological problems, infection etc.To prevent this, some drugs such as benzodiazepines have proved themselves useful, but they have their share of adverse effects. Melatonin is a new addition in the armamentarium of the anaesthesiologist. This study will compare Melatonin with a placebo for preoperative anxiolysis.